2015
DOI: 10.1177/0194599814567302
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pressure‐Induced Cranial Neuropathies from Allergic Fungal Rhinosinusitis

Abstract: Bone erosion of the sphenoid sinus walls by AFRS can lead to compression of surrounding neural structures producing cranial neuropathies. Identification of these symptoms and prompt surgical decompression and removal of disease, along with aggressive medical therapy, provided excellent outcomes in the current series of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The T2 signal void is also observed, due to a high concentration of various metals concentrated by the fungal organism, as well as a high protein and dry content of the allergic mucin 24. Bone erosion with bone remodeling is one of the most common clinical features of AFS which was reported in up to 50% of patients 26. Thus, AFS in sphenoid sinus can easily cause compressive symptoms of cranial neuropathies which surround the sphenoid sinus.…”
Section: Diseases Of Chronic Sphenoid Rhinosinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…The T2 signal void is also observed, due to a high concentration of various metals concentrated by the fungal organism, as well as a high protein and dry content of the allergic mucin 24. Bone erosion with bone remodeling is one of the most common clinical features of AFS which was reported in up to 50% of patients 26. Thus, AFS in sphenoid sinus can easily cause compressive symptoms of cranial neuropathies which surround the sphenoid sinus.…”
Section: Diseases Of Chronic Sphenoid Rhinosinusitismentioning
confidence: 99%
“…Thus, AFS in sphenoid sinus can easily cause compressive symptoms of cranial neuropathies which surround the sphenoid sinus. It was reported that cranial neuropathies develop at 10% of the sphenoid AFS with bone erosion 26. Hyperprolactinemia and gynecomastia secondary to AFS compression of the pituitary gland were also reported as presenting symptoms of sphenoid AFS 27,28.…”
Section: Diseases Of Chronic Sphenoid Rhinosinusitismentioning
confidence: 99%
“…AFRS is a non-invasive fungal sinusitis, and the process of bone erosion is usually attributed to pressure atrophy and inflammatory mediators induced by the accumulated fungal debris. However, PNS mucosa and periosteum are usually intact [5,[17][18]. Bone loss of the sphenoid wall may lead to multiple cranial neuropathies as a result of the pressure of fungal debris on the surrounding neuronal structures [18].…”
Section: Discussionmentioning
confidence: 99%
“…SAFRS can easily compress the cranial nerves. It had been documented that cranial neuropathies occur in 10% of cases of SAFRS with bone erosion [17]. Endoscopic surgery has become the fundamental approach for SAFRS.…”
Section: Allergic Fungal Sinusitismentioning
confidence: 99%